At the onset of the Micoquian in Central Europe: raw material constraints and technological versatility at Neumark-Nord 2/0 (Germany) - Picin, A. (Materiale și Cercetări Arheologice)
After the Eemian, Neanderthals of Central Europe produced new stone tools for coping with the increased seasonality and climatic deterioration of the Last Glacial. This new cultural tradition is named Micoquian, and is characterized by a broad range of asymmetric backed bifaces, foliate artefacts and bifacial scrapers. Despite the abundant number of sites and the broad geographical expansion, technological information on the early stages of development of the Micoquian are still few. This paper presents new data on the lithic assemblage of Neumark-Nord NN2/ 0, a Micoquian occupation dated to the MIS 5c/ 5a. The results point out a technical continuity with the previous Eemian settlements whereas the production of backed bifaces shows to be associated to new strategies of raw material economy in the technological context of Quina scrapers. This behaviour is different from other sites in Central Europe suggesting that the emergence of the Micoquian at the beginning of the Weichselian followed different trajectories